Uncanny fairy tales : hybrid wonders in the mirror - Arnavas, Francesca (New York, NY : Routledge, 2024)
"There are fairy tales that surprise, destabilise, or even shock us: these are uncanny fairy tales that manipulate familiar stories in creative and bewildering ways in order to express new meanings. This work analyses these tales basing its approach on a reformulation of Freud's concept of the uncanny. Through a cognitive outlook the employed theoretical framework provides new perspectives on the study of experimental literary fairy tales. Considering English-language literature, complex and unsettling re-interpretations of the fairy-tale discourse began to appear during the Victorian Age, later resurfacing as a postmodern trend. This research individuates uncanny-related narrative techniques and cognitive responses as means to decodify and explore these tales, and as ways to discover unseen connections between Victorian and postmodern texts. The new theorisation of the uncanny is linked with three sub-concepts: mirror, hybridity, and wonder, which function as tools to describe and investigate the cognitive and emotional entanglements characterising enigmatic and disorienting fairy tales"--
The shell in the woods: questioning the "unnatural" through uncanny fairy tales' mirrors, wonder, and hybridity -- Halls of mirrors: uncanny glassworlds in the castles of the mind -- Fairy brides, floating princesses, Jabberwocks: hybrid uncanniness and fairyland pastiches -- Uncanny wonders: puzzling lands, dragons, and dreams.
Keywords: Fairy tales -- Psychological aspects; Fairy tales in literature; Uncanny, The (Psychoanalysis), in literature; FICTION / Fairy Tales, Folklore & Mythology; LITERARY CRITICISM / General